2006
DOI: 10.1007/s00228-005-0084-9
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of piperaquine after repeated oral administration of the antimalarial combination CV8 in 12 healthy male subjects

Abstract: Piperaquine pharmacokinetics after repeated oral doses were characterized by multiple concentration peaks and multiphasic disposition, resulting in a long terminal half-life. Sustained exposure to the drug after treatment should be taken into account when designing future clinical studies, e.g. duration of follow-up, and may also drive resistance development in areas of high malaria transmission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
40
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 17 publications
6
40
0
Order By: Relevance
“…Furthermore, we have shown that in our P. berghei model the parasites had the capacity to rapidly become resistant to PQ, as indicated by inadequate parasite suppression upon retreatment. These findings are similar to clinical observations that showed that the long t 1/2 of PQ predisposes parasites to the emergence of drug resistance, as was evident with PQ monotherapy in China in the 1970s (4,6,7,26).…”
supporting
confidence: 88%
“…Furthermore, we have shown that in our P. berghei model the parasites had the capacity to rapidly become resistant to PQ, as indicated by inadequate parasite suppression upon retreatment. These findings are similar to clinical observations that showed that the long t 1/2 of PQ predisposes parasites to the emergence of drug resistance, as was evident with PQ monotherapy in China in the 1970s (4,6,7,26).…”
supporting
confidence: 88%
“…Most previous studies have used a two-compartment model (28,31,44). One study in healthy adults found that, although a three-compartment model represented the postadministration profile better, there were insufficient data to support its use over a two-compartment model (38). The mean elimination t 1/2 , a parameter influenced by the duration of sampling (45), was 512 h, a value within the previously reported range of 224 to 667 h (1,14,25,28,31,34,38,44).…”
Section: Discussionmentioning
confidence: 85%
“…One study in healthy adults found that, although a three-compartment model represented the postadministration profile better, there were insufficient data to support its use over a two-compartment model (38). The mean elimination t 1/2 , a parameter influenced by the duration of sampling (45), was 512 h, a value within the previously reported range of 224 to 667 h (1,14,25,28,31,34,38,44). Since there was substantial variability in the absorption phase of the plasma PQ concentration profile, a transit compartment model was tested and proved better than simpler absorption models that used lag time, as has been found in studies of other drugs (39).…”
Section: Discussionmentioning
confidence: 99%
“…We kept our PNG women fasting for 2 h after dosing, and in a healthy volunteer population pharmacokinetic study in which Vietnamese subjects were also kept fasting for 2 h postdose, there was also no evidence of a time-dependent increase in bioavailability (46). Food intake was not controlled in the Thai study (14).…”
Section: Discussionmentioning
confidence: 99%